Presence of Tetracycline and Sulfonamide Resistance Genes in Salmonella spp.: Literature Review - Sabrina Lunara Santos Pavelquesi; Ana Carolina Almeida de Oliveira Ferreira; Angeislenie Ricelle Magalhães Rodrigues; Calliandra Maria de Souza Silva; Daniela Castilho Orsi; Izabel Cristina Rodrigues da Silva (MDPI AG, 2021)
Tetracyclines and sulfonamides are broad-spectrum antibacterial agents which have been used to treat bacterial infections for over half a century. The widespread use of tetracyclines and sulfonamides led to the emergence of resistance in a diverse group of bacteria. This resistance can be studied by searching for resistance genes present in the bacteria responsible for different resistance mechanisms. Salmonella is one of the leading bacteria causing foodborne diseases worldwide, and its resistance to tetracyclines and sulfonamides has been widely reported. The literature review searched the Virtual Health Library for articles with specific data in the studied samples: the resistance genes found, the primers used in PCR, and the thermocycler conditions. The results revealed that Salmonella presented high rates of resistance to tetracycline and sulfonamide, and the most frequent samples used to isolate Salmonella were poultry and pork. The tetracycline resistance genes most frequently detected from Salmonella spp. were tetA followed by tetB. The gene sul1 followed by sul2 were the most frequently sulfonamide resistance genes present in Salmonella. These genes are associated with plasmids, transposons, or both, and are often conjugative, highlighting the transference potential of these genes to other bacteria, environments, animals, and humans.